A Particular Reading of the Theory of Trans-Substantial Motion with the Extension of the Theory of Emanation (al-Fayḍ) in Avicenna’s Philosophy - Muhammad Jafar Jamehbozorgi (آموزه‌‌های فلسفه اسلامي)
The theory of trans-substantial motion (al-harakat al-jawhariyyah) has been established based on the methodical principles of al-hikmat al- muta'āliyah (transcendent theosophy) such as the primacy of existence (asalat al-wujud) and tashkik (gradation) in objective truth (reality) of wujud (existence). Although Avicenna has never attempted to justify the integrated theory named the theory of trans-substantial motion (al-harakat al-jawhariyyah) but it seems that the pivot theory of emanation (al-fayḍ) which is counted as the most important theory in the centre of the philosophical thought can present a modern image of trans-substantial motion (al-harakat al-jawhariyyah). In Avicenna’s innovated image, the motion of the material world is the extension of the constant and continuous emanation (al-fayḍ) of almighty God and successive origination in the material world shows itself in the form of motion. Also, according to Avicenna’s opinion, the problems such as the consecutiveness of moments (tatalî anat) or adherence of causes at the same time make the theory of generation and corruption confront main problems as it cannot be considered the transformation of forms in substance (jawhar) without imagining a gradual matter or at the same time. There are statements that directly imply motion in substance and also, the unity of the moving body and mover in nature that can indicate Avicenna’s tendency to accept trans-substantial motion (al-harakat al-jawhariyyah).